The Contribution of Experiential Learning to the Development of Cognitive and Social Skills in Secondary Education: A Case Study - Gianna Voukelatou (MDPI AG, 2019)
This paper is an attempt to approach the concept of experiential learning and describes the implementation of the project teaching method in a secondary school in Athens. In the framework of this study, we carried out qualitative research using the method of in-depth interview. We aimed at recording the views, perceptions, feelings and attitudes of 20 students that participated in the project “Traditional dances from different parts of Greece.” The results showed the significant impact of experiential learning on acquiring knowledge and developing social skills and students’ attitudes, while contributing to the promotion of cultural heritage and the values of tradition. This is an original research study that depicts experiential learning in teaching as well as analyzing the teaching method of the project in combination with other different experiential/energetic educational techniques. In general, trainers and scientists of pedagogy and school psychology can use the results to design and implement educational programs in schools of all educational levels based on the experiential teaching method of learning.